Initial presentation of Hodgkin’s Lymphoma as Extradural Spinal Cord Compression: A case report - Mukherjee, Rishav; Chowdhury, Sampurna (Asian Journal of Medical Sciences, 2020)
A 23 year old female presented with acute onset paraparesis. She denied any history of fever, weight loss or drenching night sweats. Neither did she have any obvious lymphadenopathy on general examination. Chest Xray was however suggestive of mediastinal widening and her MRI spine showed metastases with superior mediastinal SOL. Biopsy of this SOL ultimately revealed classical Hodgkin lymphoma. Thus this was a very unusual initial presentation of Hodgkin lymphoma presenting as Epidural Spinal Cord Compression. Hasenclever IPS score was 2. Patient was treated with radiotherapy followed by ABVD chemotherapy and achieved remission in 3months.